RESILIENCE ON REEL: REFRAMING ETHNIC VIOLENCE THROUGH WOMEN’S MEMORY IN BODO CINEMA - Goyary, Senwarn Sun; Daimari, Perosh Jimmy (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This research examines the representation of women within Bodo-language films produced about the Bodoland Movement; a mid-to-late twentieth century movement for self-autonomy for the Bodoland region of Assam, India. Utilizing a combination of feminist film theories and cultural trauma studies as theoretical frameworks, this research utilizes a qualitative method of textual analysis of selected Bodo-language films to assess how women's roles, experiences, and agency are represented during the time of the Bodoland Movement and the subsequent ethnic insurgency/conflict. The films are analyzed for narrative and visual representations of gender, memory, and trauma. Results indicated that Bodo filmmakers have challenged traditional gender stereotyping in their depiction of women's agency and memory; instead of being presented simply as passive victims of violence, female characters in the films analyzed are presented as survivors who are capable of resilience and hope. As such, the films provide an "afterlife" of the conflict experienced during the Bodoland Movement – providing a powerful narrative of survival rather than a linear history of trauma. This research provides a more nuanced understanding of the gender dynamics present in Bodo cinema and demonstrates that the portrayal of women in Bodoland movement films reflects the intersectionality of gender, ethnicity and political upheaval and serves as a platform for collective memory and trauma.